AB0432 BURDEN OF ILLNESS AND CURRENT UNMET NEEDS AMONG PATIENTS WITH RHEUMATOID ARTHRITIS TREATED WITH CONVENTIONAL AND ADVANCED DISEASE-MODIFYING THERAPIES: A TARGETED LITERATURE REVIEW. (June 2019) - Ostor, Andrew; Sawant, Ruta; Gadhia, Alisha; Zeidman, Ruth; Garg, Vishvas; Wallace, Matthew
Abstract : Background: The development of advanced therapies for the treatment of moderate to severe rheumatoid arthritis (RA) has changed the paradigm of management goals for the condition. However, even with currently available therapies, many patients fail to achieve adequate improvement or disease remission, and thus residual unmet needs exist. Objectives: To examine the burden of RA with respect to the clinical, humanistic, and economic outcomes among RA patients treated with conventional and advanced disease-modifying therapies. Methods: A targeted review of the literature published between January 2013 and September 2018 was conducted. EMBASE and MEDLINE databases were searched using terms related to the clinical, humanistic, and economic outcomes associated with conventional and advanced disease-modifying therapies currently available for moderate to severe RA. The search was limited to English-language articles, which reported data from France, Germany, Italy, Spain, United Kingdom, Sweden, Israel, Canada, Brazil, Japan, and Australia. This returned 1, 833 records which were assessed for relevance in terms of study methodology, patient population, and outcomes. Results: A total of 48 articles were included in the qualitative synthesis. Across these studies, disease activity score (DAS) remission rates (DAS28 ≤2.6) ranged from 14.7% to 26.4% over 6–12 months and 10.2% to 53.4% over 3–20 months for patients treated with conventional synthetic disease-modifying antirheumatic drug (csDMARD) monotherapies and biologic monotherapies, respectively. Figure 1 presents country-specific DAS28 remission rates for some of the included regions. Clinical disease activity index (CDAI) remission rates (CDAI ≤2.8) were reported to be <50% among patients who received biologics for a period of up to 12 months. The unemployment rate due to RA was as high as 58.3%, and employed patients lost 1.7 to 16.0 workdays per month at baseline. Following treatment with biologic therapy (over 24–104 weeks), employed patients lost 0.5 to 8.0 working days per month. Costs of treatment with advanced therapies were routinely investigated, but limited data were available regarding the economic burden associated with outcomes such as disability, depression, lack of sleep, and anxiety among RA patients treated with advanced therapies. Conclusion: Despite advanced treatments, a significant proportion of the RA patient population do not achieve disease remission, and face the substantial burden of reduced productivity and lost work days. Acknowledgement: The design, study conduct, and financial support for the study were provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of this publication. Disclosure of Interests: Andrew Ostor Consultant for: AbbVie, BMS, Roche, Janssen, Lilly, Novartis, Pfizer, UCB, Gilead, Paradigm, Ruta Sawant Shareholder of: AbbVie, Employee of: AbbVie, Alisha Gadhia Employee of: Covance Market Access & Phase IV Solutions, which has received consultancy fees from AbbVie, Ruth Zeidman Employee of: Covance Market Access & Phase IV Solutions, which has received consultancy fees from AbbVie, Vishvas Garg Shareholder of: AbbVie, Employee of: AbbVie, Matthew Wallace Employee of: Covance Market Access & Phase IV Solutions, which has received consultancy fees from AbbVie